(untitled) (Revista Sistemas de Producción Agroecológicos, 2023)
A neoplasm is an abnormal formation of a new tissue of a tumor nature, it should be noted that when we mention Oncology it refers to cancer and this can be benign or malignant, the most frequent are breast carcinomas, carcinomas located in different parts of the skin, lymphomas and mast cell tumors, among others. In this last point, mast cell tumors are tumors that are frequently found in the skin as the site of origin and are frequently bulging masses of different sizes that do not exceed 3 or 4 cm. They usually present with erythema, hypotrichosis, or alopecia. . This report presents a case of a 5-year-old Basset Hound dog weighing 28 kilograms admitted to the veterinary clinical center of the Universidad de los Llanos, with a mass located in the dorsal region of the proximal third of the tail. , of semi-hard consistency, with subcutaneous fluid, rounded in shape and 2 cm in diameter with hypotrichosis, for which a wide surgical edge was operated with a reconstructive technique. After surgery, the patient spent a short time in the veterinary clinical center. with a satisfactory recovery.